Traditional Chinese Medicine and Gut Microbiome: Their Respective and Concert Effects on Healthcare - Zhang, Runzhi; Gao, Xi; Bai, Hong; Ning, Kang (Frontiers in Pharmacology, 2020)
Advances in systems biology, particularly based on the omics approaches, has resulted in a paradigm shift in both Traditional Chinese Medicine (TCM) and the gut microbiome research. In line with this paradigm shift, the importance of TCM and gut microbiome in healthcare, as well as their interplay, has become clearer. In this review, we first summarize the current status of three topics briefly: microbiome, TCM, relationship of TCM and microbiome. Second, we focused on TCM's therapeutic effects and gut microbiome's mediation roles, including the relationships among diet, gut microbiome and health care. Third, we summarize databases and tools that could help in molecular understanding of the effects of TCM and gut microbiome on diagnosis and treatment. Finally, we introduce the effects of gut microbiome on TCM and host health, with two case studies, one on the metabolic effect of gut microbiome on TCM, and another on cancer treatment. In summary, we have reviewed the current status of the two components of healthcare: TCM and gut microbiome, as well as their concert effects. It is quite clear that as a holobiont, the maintenance of the health status of human would depend heavily on TCM, gut microbiome, and their combined effects.